Rerajahan Aesthetics as an Idea for Creating Painting Works - Aprianta, I Putu Gede Ivan Ayestha; Kondra, I Wayan; Sucipta, I Wayan Adi (PROGRAM STUDI SENI MURNI ISI DENPASAR, 2024)
This independent study report raises the theme of Rerajahan Aesthetics as an Idea for Creating Painting Works, starting from raising ideas around rerajahan. All aspects of Balinese life are imbued with Hinduism, which indirectly gives birth to a socio-religious culture. Various cultural elements were born due to the demands of religious needs. Art as an element of culture was also born due to the demands of religious activities. This has encouraged the creation of various forms of symbolic-magical art which are representations of something abstract. One of them is in the form of pictures or writing which is commonly called Rerajahan. For the Balinese people, rerajahan, apart from being a means of religious ceremonies, is also believed to have very high supernatural powers. This believed power functions as a means of suggestion to achieve certain desires or goals. In this case, the effect of rerajahan is that it is able to become a source of ideas for artists in creating modern works of art without abandoning the traditional values behind it. Rerajahan is also a very inspiring work of traditional art, and a source of ideas for some Balinese artists in creating individual works.